2020
DOI: 10.3390/ijerph17072256
|View full text |Cite
|
Sign up to set email alerts
|

Peak Match Demands in Young Basketball Players: Approach and Applications

Abstract: Background: The aim of this study is to describe the peak match demands and compare them with average demands in basketball players, from an external load point of view, using different time windows. Another objective is to determine whether there are differences between positions and to provide an approach for practical applications. Methods: During this observational study, each player wore a micro technology device. We collected data from 12 male basketball players (mean ± SD: age 17.56 ± 0.67 years, height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 51 publications
0
36
1
1
Order By: Relevance
“…As previous findings confirmed, basketball is a sport where most of play time is spent in walking and standing activities [1,5,8]. However, the capacity to be exposed to accelerations, decelerations, change of directions, landings, peak demands, or jumps is vital for on-court success, due to the intermittent high-intensity nature of most actions and basketball specific movements [1,[46][47][48][49][50][51].…”
Section: Specific Thresholdsmentioning
confidence: 72%
“…As previous findings confirmed, basketball is a sport where most of play time is spent in walking and standing activities [1,5,8]. However, the capacity to be exposed to accelerations, decelerations, change of directions, landings, peak demands, or jumps is vital for on-court success, due to the intermittent high-intensity nature of most actions and basketball specific movements [1,[46][47][48][49][50][51].…”
Section: Specific Thresholdsmentioning
confidence: 72%
“…A correct training session design related to the technical-tactical-physical purpose and the competition is important for workload managing during competitive microcycles [ 4 , 5 , 64 ]. In this sense, the use of effective strategies can help to anticipate the higher peak of performance in competition [ 67 , 68 , 94 ]. Also, it is important to monitor the player during all the training phases to assure the efficacy of the training effectiveness [ 95 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…12.7%) cited the reliability and validity of other devices that were not used in their respective research. Investigations measured with Optimeye and Team 2.5 devices (Catapult Sports) [ 62 , 67 , 69 , 73 , 74 , 104 , 110 112 ], ZXY Sportracking (Radionor Communications) [ 26 ], X8-mini (Gulfcoast Data Concept) [ 24 , 25 , 29 ], Actilife v12 (ActiGraph) [ 75 ], and Viper V2 (StatSport) [ 76 ] cited the validity study of Barrett et al [ 19 ] and reliability of Boyd et al [ 16 ] realized with MinimaxX devices (Catapult Sports). Noteworthy, 34.7% of the studies did not report the validity or reliability and did also not refer to literature findings for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 122 included studies, 37 reported excluding some participants based on specific criteria. Participant exclusion was reported in 19 studies based on percentage of participation in training or competition [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], 7 studies based on player rotation status during competition (i.e. starter, bench, active in game, not substituted) [35][36][37][38][39][40][41], 5 studies based on missed sessions (i.e.…”
Section: Participant Inclusionmentioning
confidence: 99%